Psychic tools in the workplace - Edward, John (John J.) (Edgewood, NY : Ingenious Designs LLC, 2007)
Teaches the tools and awareness for psychic ability.
DVD 5. Psychic tools in the workplace --
DVDs.
107386
Keywords: Edward, John; Spiritualism